Improving Student's Conceptual Understanding and Metacognitive Strategies through Quantum Learning Model with Concept Map Techniques - Achmad Aenal Yaqin (SEAMEO QITEP in Science, 2022)
Nowadays, we commonly find students’ low interest toward science learning, students’ low understanding of science concept, and low impact of learning process toward students’ thinking skills. This study aims to identify the improvement of students’ conceptual understanding and metacognitive when applying quantum learning model with mind mapping at learning process. This study also describes the metacognitive strategies in quantum learning model using mind map. A mixed methodology was used in this study. The results show that students who studied using quantum learning model with mind mapping have higher conceptual understanding and metacognitive improvement. The steps in the quantum learning model can improve students' metacognitive strategies. The result provide suggestion to other teachers to alternatively use quantum learning model with mind mapping to improved students’ conceptual understanding and metacognitive.